1998
DOI: 10.1046/j.1365-2249.1998.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

A variety of cytokines and immunologically relevant surface molecules are expressed by normal human skeletal muscle cells under proinflammatory stimuli

Abstract: SUMMARYMuscle is an attractive target for gene therapy and for immunization with DNA vaccines and is also the target of immunological injury in myositis. It is important therefore to understand the immunologic capabilities of muscle cells themselves. In this study, we show that proinflammatory stimuli induce the expression of other cytokines such as IL-6, transforming growth factor-beta (TGF-b), and granulocytemacrophage colony-stimulating factor (GM-CSF) by muscle cells themselves, as well as the upregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 23 publications
3
120
2
9
Order By: Relevance
“…46 ICAM-1 can be shed by the cells and detected as a soluble plasma molecule (sICAM-1). 47 The production of both forms is upregulated in human myoblasts on stimulation with IL-1b, IL-4, IL-6, IFN-g and LPS ( Figure 2a); 42,48 increased levels of sICAM-1 have been detected in the plasma of patients with idiopathic inflammatory myopathies. 49 The binding of sICAM-1 to LFA-1-expressing cells can modulate immune functions through the inhibition of T-cell interactions with APC or target cells.…”
Section: Muscle Cells Recruit Leukocytesmentioning
confidence: 96%
See 3 more Smart Citations
“…46 ICAM-1 can be shed by the cells and detected as a soluble plasma molecule (sICAM-1). 47 The production of both forms is upregulated in human myoblasts on stimulation with IL-1b, IL-4, IL-6, IFN-g and LPS ( Figure 2a); 42,48 increased levels of sICAM-1 have been detected in the plasma of patients with idiopathic inflammatory myopathies. 49 The binding of sICAM-1 to LFA-1-expressing cells can modulate immune functions through the inhibition of T-cell interactions with APC or target cells.…”
Section: Muscle Cells Recruit Leukocytesmentioning
confidence: 96%
“…1, 38,42 Intercellular adhesion molecule-1 (ICAM-1) molecules, whose ligand on T cells is LFA-1, are commonly present not only on professional APC, such as macrophages and DCs, but also on target cells involved in inflammatory processes. 43 They are absent in normal muscles, but are observed in all inflammatory myopathies, where they are expressed not only by the endothelium of perimysial arterioles and venules, but also by muscle fibres, especially the non-necrotic ones, which are invaded by mononuclear cells.…”
Section: Muscle Cells Recruit Leukocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…MHC-I molecules are necessary for antigen-specific T cell-mediated cytotoxicity and can mediate a response against surface antigens on myofibres [10]. Previous studies have also shown that MHC-I can behave as a pathogenic molecule in its own right since its expression can precede lymphocytic cell infiltration, and transgenic mice overexpressing MHC-I have been shown to develop a severe myopathy even in the absence of inflammation [11][12][13][14].…”
Section: Mhc-i Is Expressed But Is Undetectable Immunohistochemicallymentioning
confidence: 99%